Caso para diagnóstico? Case for diagnosis - Weber Soares Coelho; Thaiz Gava Rigoni Gurtler; Lucia Martins Diniz; João Basílio de Sousa Filho (Sociedade Brasileira de Dermatologia, 2008)
Mulher branca de 30 anos de idade há 15 anos apresentando lesões com depressões e herniações anulares, atróficas, bem circunscritas em pele previamente normal, predominando na região cervical e tronco; sem história familiar. Exames laboratoriais sem alterações e histopatológico com infiltrado inflamatório discreto na derme. Coloração com orceína evidenciou fibras elásticas fragmentadas e encurtadas. Após correlação anatomoclínica confirmou-se o diagnóstico de anetodermia de Schweninger-Buzzi. A 30-year old woman with a 15-year history of atrophic, well-circumscribed annular lesions, with depressions and herniations, , in previously normal skin is presented. The lesions were predominant in the neck region and trunk; there was no familiar history. Laboratory examination was normal or negative and histological examination displayed discrete inflammatory infiltration on the dermis. Orceina stain showed fragmented and shortened elastic fibers. Diagnosis of anetodermia, Schweninger- Buzzi type, was confirmed after clinic-histological correlation.